2021
DOI: 10.1002/aesr.202100172
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Inkjet Printing of Electrochromic Smart Windows for Building Energy Modulation

Abstract: Electrochromic smart windows are promising for green buildings due to energy efficiency, long optical memory effect, and tunable optical transmission. However, their wide application in buildings is impeded by challenges in scalability, cost‐effectiveness, and limited optical contrast. Quantitative field study of energy savings enabled by electrochromic smart windows in buildings is also lacking. Herein, with the established inkjet printing procedures, electrochromic smart windows (900 cm2) are fabricated. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 24 publications
(42 reference statements)
0
27
0
Order By: Relevance
“…On reversing the bias polarity, Li-ions starts to get removed from the NbO x −ITO film, which leads the smart window to come back to its bright mode (Figure 2d). Similar devices can be fabricated using large-area (900 cm 2 ) inkjet printing methods, 66 making the design scalable. Field test results show outstanding EC performance, including a large optical contrast of ∼60% and long optical memory retention, with less than 10% of transmittance maintained after 7 h. Interestingly, these large-area ECDs exhibited a heat gain reduction of 42.3% and a cooling load savings of 28.9% on a sunny day, compared to a regular double-glazed units-based reference testbed.…”
Section: Savingmentioning
confidence: 99%
“…On reversing the bias polarity, Li-ions starts to get removed from the NbO x −ITO film, which leads the smart window to come back to its bright mode (Figure 2d). Similar devices can be fabricated using large-area (900 cm 2 ) inkjet printing methods, 66 making the design scalable. Field test results show outstanding EC performance, including a large optical contrast of ∼60% and long optical memory retention, with less than 10% of transmittance maintained after 7 h. Interestingly, these large-area ECDs exhibited a heat gain reduction of 42.3% and a cooling load savings of 28.9% on a sunny day, compared to a regular double-glazed units-based reference testbed.…”
Section: Savingmentioning
confidence: 99%
“…[8][9][10][11] Another research approach in the field of electrochromics is the manufacturing of displays via printing and coating processes. [5,[12][13][14][15] Utilizing such deposition techniques to fabricate EC displays may enable commercialization due to the allowance of a drastically lowered cost per device. Techniques such as inkjet printing, slot-die coating, and screen printing have been prevalent in the scientific literature to produce all-printed EC devices.…”
Section: Introductionmentioning
confidence: 99%
“…For example, John R. Reynolds et al in 2009 reported roll-to-roll screen printed ECD 17 and Pooi See Lee et al in 2021 reported inkjet printing of large-area ECDs. 18 Other solution processes include various wet coating methods such as dip coating, spin coating and spray coating. 19,20 A solid electrolyte layer is the key functional layer of the ECD, which plays the role of providing ion transport channels, and is much safer than the liquid electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…For example, John R. Reynolds et al in 2009 reported roll-to-roll screen printed ECD 17 and Pooi See Lee et al in 2021 reported inkjet printing of large-area ECDs. 18 Other solution processes include various wet coating methods such as dip coating, spin coating and spray coating. 19,20…”
Section: Introductionmentioning
confidence: 99%